Anatomical Mapping for Atrial Fibrillation Ablation: A Head‐to‐Head Comparison of Ultrasound‐Assisted Reconstruction versus Fast Anatomical Mapping. Issue 2 (2nd December 2014) - RORDORF, ROBERTO; CHIEFFO, ENRICO; SAVASTANO, SIMONE; VICENTINI, ALESSANDRO; PETRACCI, BARBARA; DE REGIBUS, VALENTINA; VALENTINI, ADELE; KLERSY, CATHERINE; DORE, ROBERTO; LANDOLINA, MAURIZIO
<x xml:space="preserve">Abstract</x> Background Accuracy in left atrial (LA) anatomical reconstruction is crucial to the safe and effective performance of catheter ablation of atrial fibrillation (AF). The aim of this study was to evaluate the accuracy of LA reconstruction performed with intracardiac echocardiography (ICE) as compared to fast anatomical mapping (FAM) both integrated in the CARTO mapping system (Biosense Webster, Diamond Bar, CA, USA). Methods A multislice computed tomography (MSCT) was preacquired from 29 patients with AF who underwent catheter ablation and 3D‐LA geometry was reconstructed using both ICE and FAM separately. The accuracy of the LA anatomical definition was evaluated by comparing LA volumes, LA and pulmonary vein (PV) diameters obtained using ICE and FAM versus MSCT (gold standard). Results Anterior‐posterior and superior‐inferior LA diameters were shorter in ICE versus MSCT (32 ± 10 vs 46 ± 9 mm and 48 ± 7 vs 53 ± 7 mm, P < 0.01) but similar in FAM versus MSCT (45 ± 9 vs 46 ± 9 mm and 52 ± 10 vs 53 ± 7 mm). Latero‐septal LA diameter was similar in ICE versus MSCT (63 ± 11 vs 63 ± 9 mm) but larger in FAM versus MSCT (69 ± 9 vs 63 ± 9 mm, P < 0.001). LA volume was lower in ICE versus MSCT (73 ± 30 mL vs 116 ± 45 mL, P < 0.0001) and slightly larger in FAM versus MSCT (132 ± 45 vs 116 ± 45 mL, P = 0.06). PV diameters were similar in FAM versus MSCT but significantly underestimated with ICE. Conclusions Overall accuracy in the LA and PV anatomical reconstruction was found to be superior with FAM compared to ICE‐guided approach. ICE resulted in a significant underestimate of both LA and PV dimensions, while FAM slightly overestimated LA geometry.